1987
DOI: 10.1288/00005537-198703000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Acute bilateral deafness with nephritis: A human temporal bone study

Abstract: Temporal bone pathology is described in a 37‐year‐old man who had acute, bilateral, profound sensorineural hearing loss without improvement 4 months before death. The patient had suffered from low complement nephritis, for which he had received prednisolone therapy. Autopsy revealed malignant lymphoma with non‐Hodgkin's type, membranous proliferative glomerulonephritis and necrotizing vasculitis of middle and small arteries. In the temporal bone study, pathological changes were limited to the cochlear region. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…It appears that CIC deposits in the blood vessel of the stria vascularis damage the capillary endothelium, increase the vascular permeability, and secondarily result in endolymphatic hydrops. The histopathological features observed in the patients 21–27 and in animal models 28 with immunomediated inner‐ear disorders support this vascular pathogenesis. In fact, temporal bone studies have shown that in such cases the most common findings were vasculitis in the internal auditory artery and capillary damage within the stria vascularis, followed by spiral ganglion cell degeneration, atrophy of the organ of Corti, collapse of Reissner's membrane, distortion of the tectoral membrane, and endolymphatic hydrops with atrophy of the surface epithelium of the endolymphatic duct.…”
Section: Discussionmentioning
confidence: 52%
“…It appears that CIC deposits in the blood vessel of the stria vascularis damage the capillary endothelium, increase the vascular permeability, and secondarily result in endolymphatic hydrops. The histopathological features observed in the patients 21–27 and in animal models 28 with immunomediated inner‐ear disorders support this vascular pathogenesis. In fact, temporal bone studies have shown that in such cases the most common findings were vasculitis in the internal auditory artery and capillary damage within the stria vascularis, followed by spiral ganglion cell degeneration, atrophy of the organ of Corti, collapse of Reissner's membrane, distortion of the tectoral membrane, and endolymphatic hydrops with atrophy of the surface epithelium of the endolymphatic duct.…”
Section: Discussionmentioning
confidence: 52%
“…Although abnormal otic capsule bone formation has been described in various patients afflicted with autoimmune diseases (Cogan's syndrome, polyarteritis nodosa, systemic lupus erythematosus, and Wegener's granulomatosis':"), temporal bone immunohistochemical studies have been done in only one case. Yanagita et al 10 found no IgM staining in the pathologic temporal bone of a polyarteritis nodosa individual, in spite of pronounced IgG and complement staining of the kidney. Their conclusion was that cochlear sensorineural and bone pathology were the result of a necrotizing vasculitis and not direct immune reactions, such as autoantibodies.…”
Section: Discussionmentioning
confidence: 97%
“…Temporal bone histopathological studies have shown arteritis of the internal auditory artery with widespread cochlear and vestibular changes and new bone formation 63,64 . Yanagita and Yokoi reported complete disappearance of the organ of Corti and fibrosis of the apical turn 65 . From the above findings, vasculitis appears to be the possible underlying mechanism of the SNHL.…”
Section: Clinical Featuresmentioning
confidence: 92%